Laying the Tracks: The Political Economy of Railway Development in Ethiopia's Railway Sector and Implications for Technology Transfer - Yunnan Chen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Explore Yunnan Chen's analysis of railway construction as a manifestation of China's economic statecraft in Africa. As African leaders have eagerly leveraged the railway sector, this paper looks through the lens of African agency to examine the case of Ethiopia's Chinese-financed railway projects, including the Addis- Djibouti Railway, contrasting it to Ethiopia's experience with subsequent European/Turkish financed projects. Chen shows the opportunities, missed and taken, by Ethiopian actors in leveraging external partners, focusing on areas of technology and skills transfer. Ultimately, the different financing arrangements entail different relationships—one politicized, one commercial—offering different scopes of bargaining power: while the political relationship offers greater flexibility regarding financing, the commercial project has been more successful for exercising agency in relation to contractors.
Keywords: 330